Bio-cake layer based ultrafiltration in treating iron-and manganese-containing groundwater: Fast ripening and shock loading. (April 2021) - Tang, Xiaobin; Qiao, Jialiang; Wang, Jinlong; Huang, Kaijie; Guo, Yuanqing; Xu, Daliang; Li, Guibai; Liang, Heng
Abstract: Groundwater was a desired alternative for decentralized water supply. However, the presence of iron, manganese and ammonia significantly limited its extensive adoptions. In this study, an innovative gravity-driven membrane (GDM) process has been developed to address such problems. The results indicated that GDM process can efficiently diminish the concentrations of iron, manganese and ammonia, with average removal efficiencies of 97%, 95% and 70%, respectively, since the bio-cake layer on the membrane surface can serve as a dynamic barrier for the foulants rejection. In GDM filtration, the manganese removal was mainly attributed to the synergistic effects between the chemically auto-catalytic oxidation by manganese oxides (MnOx) and biological activity by manganese-oxidizing bacteria (MnOB). Pre-addition of MnOx particles into GDM system could significantly enhance the manganese removal and shorten its ripening time by approximately 50%. During long-term filtration, the fluxes of GDM remained stabilized (4–5 L m −2 h −1 ), and MnOx particles pre-additions could improve the stable fluxes by 23%–37%. The flux stabilization of GDM process was mainly determined by the heterogeneous structures of bio-cake layer, and the generated iron and manganese oxides would improve its heterogeneities. Furthermore, MnOx assisted GDM process conferred robust capacities in resisting the shock loading of manganese and ammonia in the feed water, and the highest concentrations of manganese and ammonia were suggested to be less than 2.96 mg/L and 0.9 mg/L, respectively. Therefore, these findings are full of relevance to develop new strategies to treat the iron- and manganese-containing groundwater and promote the extensive application of UF technology for decentralized water supply. Highlights: Bio-cake layer based UF can treat iron- and manganese-containing groundwater. Flux stabilized at 4–6 LHM with iron and manganese being reduced by>97% and >95%. MnOx can improve the porosity of bio-cake layer and result in flux stabilization. GDM conferred high capacity in resisting shock loading of manganese and ammonia. Iron, manganese and ammonia were mainly diminished by the bio-cake layer.